ENHANCING PEDAGOGICAL COMPETENCE IN PRIMARY TEACHERS: THE ROLE OF ACADEMIC SUPERVISION - Shururi; Niswanto; Nasir Usman (CV. RADJA PUBLIKA, 2024)
This study examines the role of academic supervision by supervisors in improving the pedagogical competence of elementary school teachers in Setia District, Southwest Aceh Regency. The research focuses on four key aspects: planning, implementation, follow-up, and challenges faced during the academic supervision process. The study employed a qualitative approach, collecting data through interviews, observations, and documentation. Techniques for ensuring data validity included persistent observation and triangulation. The subjects consisted of two supervisors, two principals, and four teachers from two elementary schools in the district. The key findings were: (1) Academic supervision planning by supervisors to enhance teachers' pedagogical competence was conducted at the beginning of the academic year, involving supervisors, principals, and teachers. The planning stage began with developing an academic supervision semester program through meetings with the teacher council, which was then conveyed directly by the principal. (2) In implementing academic supervision, supervisors strongly emphasized the importance of teachers' mastery of the subject matter. Therefore, supervisors paid close attention to teachers' efforts to improve their performance in carrying out their duties to achieve the goal of improving pedagogical competence. (3) Follow-up activities were part of the supervision conducted by the principals. Thus, supervisors needed tools to objectively assess and record teachers' strengths and weaknesses, which could subsequently guide individual and group coaching efforts. (4) Challenges faced included limited supervision time allocated by supervisors, lack of senior or peer teachers with the required knowledge and abilities to serve as supervisors, uneven competence levels among supervisors, and perceived subjectivity from principals.